2010
DOI: 10.1007/s10926-010-9232-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Return to Work After Occupational Injury

Abstract: There were multidimensional factors affecting RTW after occupational injury. Proper clinical treatment and rehabilitation, as well as economic and social support to facilitate workers' RTW would be the priorities upon intervention. Future studies should be conducted in larger representative samples to confirm the findings and to develop a multidisciplinary intervention strategy towards promoting RTW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 28 publications
7
42
2
2
Order By: Relevance
“…The finding of no significant relationship between injury severity and NRTW is in contrast with previous research with RTC cohorts 9, 13, 15 and the majority of research from broader injury cohorts 27,30,34,38,39 . There were, however, two studies from the wider injury literature where no relationship between injury severity and RTW was found 40, 41 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The finding of no significant relationship between injury severity and NRTW is in contrast with previous research with RTC cohorts 9, 13, 15 and the majority of research from broader injury cohorts 27,30,34,38,39 . There were, however, two studies from the wider injury literature where no relationship between injury severity and RTW was found 40, 41 .…”
Section: Discussioncontrasting
confidence: 99%
“…Disability refers to an individual's functioning, and is considered a dynamic interaction between the individual's health and environmental and/or personal factors. Therefore, early rehabilitation that addresses physical, psychological and social functioning in an integrative way may be the best approach for early intervention when targeting disability 72 .When examining the univariate predictors of NRTW, the finding that greater pain levels predict NRTW is consistent with two previous studies using RTC cohorts 15,17 and in general injury samples 18,27,30,37,39,43 . The finding that greater baseline symptom levels of anxiety 35,44 and depression 44,45 predict NRTW is consistent with previous general injury studies, however it is inconsistent with findings from van Velzen et al 41 .…”
supporting
confidence: 81%
See 1 more Smart Citation
“…It is important to bear in mind that any disability and return to work following injury are greatly influenced by several variables concerning the psycho-physical characteristics of each worker, type of injury, healthcare and rehabilitation system, physician-patient relationship, clinical case management by physician, vocational training, invalidity insurance system (particularly with regard to workers' compensation), organization and psychosocial/ physical characteristics of the work done, improvements in the working environment and companyrelated factors (e.g. employer, job role, discrimination, legal framework, labor market characteristics) (17,(35)(36)(37). In this respect, we could more specifically recognize seven groups of factors, influencing the duration of post-injury disability, to be taken into account during the medical examination prior to resuming duties: …”
Section: Health Surveillance and Occupational Injuriesmentioning
confidence: 99%
“…As a matter of fact, recent studies have revealed that, following an occupational injury, the worker is unlikely to receive appropriate and coordinated medical care, he/she is not supported and assisted by the employer when resuming his/her duties, compensation claims are not managed satisfactorily and information relevant to the task performed, to re-injury risk and the proper conditions to facilitate return to work often fail to be appropriately disclosed or discussed. The occupational physician called upon to carry out health surveillance programs should be able to promote healthy eating and proper lifestyle habits, giving advice on the proper use of medicines and responsible drinking, recommending to take breaks while driving, teaching the workers how to recognize the risk factors and the warning signs likely to slow reflexes while driving (37). In conclusion, the role of the occupational physician can be considered really complete when, as a result of his/her intervention, it is possible to identify the proper work activities and work schedules, launch work reintegration strategies, prescribe specific PPE, promote additional training and occupational rehabilitation and provide medical and psychological care.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%